Changing trends in caesarean deliveries at a tertiary care Centra: a ten year appraisal - Paudyal, Pooja; Gurung, G.; Baral, J; Rana, A (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Over the last few decades, the rise in the rates of Caesarean Sections (CS) has become a global phenomenon. The objective of this study was to follow the CS rates over the last 10 years and to compute the various indications of CS in an attempt to analyze the possible reasons for this changing trend in the institute. Methods: All deliveries that took place between April 13, 2004 to April 14, 2014 (Baisakh 2061 BS and Chaitra 2070 BS) in TUTH were retrospectively collected. Annual total number of deliveries, rates of CS, instrumental deliveries and Vaginal Birth after Caesarian Section (VBAC) along with indications for CS were computed and analyzed. Result: A total of 38,770 deliveries were conducted over ten years with 26,791 (69.10%) vaginal deliveries and 11,979 (24.80%) CS. There was a steep rise in the rates of CS from 21.04% in 2004 to 39.23% in 2014. Rates of instrumental deliveries and VBAC remained low at 0.86% to 3.35% and 0.15% to 0.7 % respectively. Fetal distress was the commonest indication of emergency CS while previous CS was the commonest indication for elective CS. Conclusion: Over the last decade, the global trend of rising CS rates was also found to be mirrored at TUTH. The causes for rise in CS rates were- increased diagnosis of fetal distress and oligohydramnios, delivery of most breech by Caesarean sections, low rates of VBAC and instrumental deliveries, complicated referrals from all over the country and last but not the least, threat of malpractice litigations. Journal of Society of Surgeons of Nepal Vol. 17, No. 2, 2014, Page: 7-11